NuMbEr ThEoRy...

Let a , b , c N a, b, c \in N be such that a 2 + b 2 = c 2 a^2 + b^2 = c^2 and c b = 1 c - b = 1 then which of the these is true?

a a is divisible by 4 4 . Finite number of ( a , b , c ) (a, b, c) exist. b b is odd. a b + b a a^b + b^a is divisible by c c .

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Zico Quintina
May 17, 2018

The triples a , b , c ) a,b,c) that solve the given system are clearly Pythagorean, and since c b = 1 c - b = 1 they must be primitive.

Using Euclid's Formula for Pythagorean triples, we know that a = m 2 n 2 , b = 2 m n a = m^2 - n^2, b = 2mn and c = m 2 + n 2 c = m^2 + n^2 for some m , n N m,n \in \mathbb{N} and m > n m > n ; in addition, as we know the triples must be primitive, we have the added conditions that m , n m,n be relatively prime and not both odd. We first disprove the three incorrect answers:

  • a a is divisible by 4 4 :

Since m m and n n are relatively prime and not both odd, we immediately get that a = m 2 n 2 a = m^2 - n^2 must be odd.

  • b b is odd :

b = 2 m n b = 2mn , so clearly b b cannot be odd.

  • A finite number of ( a , b , c ) (a,b,c) exist :

From the given condition c b = 1 c - b = 1 , we get

m 2 + n 2 2 m n = 1 ( m n ) 2 = 1 m n = 1 [We can disregard m n = - 1 as we know m > n ] \begin{aligned} m^2 + n^2 - 2mn &= 1 \\ (m - n)^2 &= 1 \\ m - n &= 1 \qquad \small \text{[We can disregard } m - n = \text{-}1 \text{ as we know } m > n] \end{aligned}

so any consecutive n , m n,m would give us a Pythagorean triple satisfying c b = 1 c - b = 1 . They would trivially be relatively prime and not both odd, so the triples would be primitive; and clearly any two different consecutive n , m n,m would give different values for c c , so the triples would all be distinct. We now show that the remaining statement must be true. We will use the fact that since m , n m,n are not both odd, b = 2 m n b = 2mn must be a multiple of 4 4 , i.e. b = 4 k b = 4k for some k N k \in \mathbb{N} .

  • a b + b a a^b + b^a must be divisible by c c :

From c b = 1 c - b = 1 we get

b - 1 ( m o d c ) b 2 1 ( m o d c ) a 2 - 1 ( m o d c ) [since a 2 + b 2 = c 2 ] \begin{aligned} b &\equiv \text{-}1 \pmod{c} \\ b^2 &\equiv \; 1 \pmod{c} \\ a^2 &\equiv \text{-}1 \pmod{c} \qquad \small \text{[since } a^2 + b^2 = c^2] \end{aligned}

which yield

b a ( - 1 ) a ( m o d c ) - 1 ( m o d c ) [because, as shown above, a must be odd.] \begin{aligned} b^a &\equiv (\text{-}1)^a \pmod{c} \\ &\equiv \: \ \text{-}1 \; \; \, \pmod {c} \qquad \small \text{[because, as shown above, } a\text{ must be odd.]} \end{aligned}

and

a b a 4 k ( m o d c ) ( a 2 ) 2 k ( m o d c ) ( - 1 ) 2 k ( m o d c ) 1 ( m o d c ) \begin{aligned} a^b &\equiv \; \; a^{4k} \; \; \pmod{c} \\ &\equiv (a^2)^{2k} \pmod{c} \\ &\equiv (\text{-}1)^{2k} \pmod{c} \\ &\equiv \; \; 1 \quad \; \pmod{c} \end{aligned}

Finally, combining the two above results, we have that a 2 + b 2 0 ( m o d c ) a^2 + b^2 \equiv 0 \pmod{c} , i.e. a 2 + b 2 a^2 + b^2 is divisible by c c .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...